Comparative Frictional Analysis of Automobile Drum and Disc Brakes - H.P. Khairnar; V.M. Phalle; S.S. Mantha (Tribology in Industry, 2016)
In the present work, a comparative frictional behaviour of drum brakes and disc brakes in automobiles has been investigated. The influential factors; contact force and friction radius were modeled for the estimation of the friction coefficient for drum as well as disc brakes. The effect of contact force and friction radius is studied with varying conditions of parameters; longitudinal force, caliper force and torque on piston side as well as non-piston side. The numerical results obtained have been compared with the similar obtained from virtual Matlab/Simulink models for drum and disc brakes. The results evidenced that friction radius predominantly affects brake pressure and thus the friction coefficient, also the increase in contact force resulted with decrease in friction coefficient both for drum and disc brakes. Further it has been found that disc brakes exhibit gradual decrease of friction coefficient due to the equitable distribution of braking effort while drum brake presents sudden variations in friction coefficient. It can be revealed that frictional behaviour of disc brake is more consistent than drum brake.